FRAnCIs calculation program with universal Raman calibration data for the determination of PVX properties of CO2–CH4–N2 and CH4–H2O–NaCl systems and their uncertainties. (November 2021) - Le, Van-Hoan; Caumon, Marie-Camille; Tarantola, Alexandre
Abstract: Many experimental calibration data linking the variation of Raman spectral parameters (i.e., peak position, peak area/intensity ratio …) with the PVX properties of pure gases or mixtures of CO2 –CH4 –N2 or CH4 –H2 O–NaCl systems have been published in literature by different laboratories. However, there is a significant discrepancy between these calibrations, leading possibly to inaccurate results when applied in another laboratory. In this paper, the inter-laboratory applicability of the existing calibration data is examined. Universal calibration data based on 78 regression equations and applicable for any Raman apparatus within any laboratory are provided in the form of a calculation program. The FRAnCIs (acronym for F luids: R aman An alysis of the C omposition of I nclusions ) Python user-friendly interface facilitates the application of these calibrations as well as to estimate the uncertainty of the measurements. Highlights: Examination of the inter-laboratory applicability of the published calibration data. Providing universal calibration data applicable in other laboratories/instruments. A calculation program for direct determination of PVX properties and uncertainty.